∫ c o s 4 ( 5 x ) d x \displaystyle \int cos^4(5x)\, dx ∫ co s 4 ( 5 x ) d x
The first-quadrant area is bounded by the curve y 2 = 4 x y^2 = 4x y 2 = 4 x , the x axis, and the line x = 4 is rotated about the y axis. Find the volume generated:
(a) By the ring method
(b) By the shell method
∫ t a n 3 x s e c 2 x d x \displaystyle \int \frac{tan^3x}{sec^2x} \, dx ∫ se c 2 x t a n 3 x d x
Evaluate ∫ x 2 c o s ( x ) d x \int x^2 \, cos(x) \, dx ∫ x 2 cos ( x ) d x
Use the disk method to find the volume of the solid of rotation by rotating the bounded area around the y-axis
y = 2 x 2 y = 2x^2 y = 2 x 2 , y = 0 y = 0 y = 0 , x = 2 x = 2 x = 2
∫ t a n 3 x s e c 3 x d x \displaystyle \int tan^3x \, sec^3x \, dx ∫ t a n 3 x se c 3 x d x
Compute ∫ x e 5 x d x \int xe^{5x}dx ∫ x e 5 x d x and ∫ π / 4 π / 3 c o s ( x ) l n ( s i n ( x ) ) d x \displaystyle \int_{\pi/4}^{\pi/3} cos(x) ln(sin(x)) \, dx ∫ π /4 π /3 cos ( x ) l n ( s in ( x )) d x
Given x 3 = y 5 + 2 x^3 = y^5 + 2 x 3 = y 5 + 2 , find the arc length from y = 1 y = 1 y = 1 to y = 3 y = 3 y = 3 and the surface area when the arc is rotated about the x-axis.
Integrate 9 − x 2 x 2 d x \frac{\sqrt{9-x^2}}{x^2} \, dx x 2 9 − x 2 d x using trigonometric substitution.
Integrate 1 x 2 x 2 + 4 d x \frac{1}{x^2 \sqrt{x^2 + 4}} \, dx x 2 x 2 + 4 1 d x using trigonometric substitution.
Simplify and integrate the expression ( x 2 + 9 ) 3 / 2 (x^2 + 9)^{3/2} ( x 2 + 9 ) 3/2 using trigonometric substitution where x = 3 tan ( θ ) x = 3\tan(\theta) x = 3 tan ( θ ) .
Evaluate the integral ∫ d t t 2 + 9 \displaystyle \int \frac{dt}{t^2 + 9} ∫ t 2 + 9 d t using trigonometric substitution.
Integrate 1 a 2 − x 2 1 \over \sqrt{a^2 - x^2} a 2 − x 2 1 .
Integrate the square root of 2 − x 2 2-x^2 2 − x 2 over x 2 x^2 x 2 .
Integrate the square root of 1 − 4 x 2 1 - 4x^2 1 − 4 x 2 .
Integrate 1 x 9 − x 2 \displaystyle \frac{1}{x \sqrt{9-x^2}} x 9 − x 2 1 .
Integrate 4 − x 2 x 2 \frac{\sqrt{4-x^2}}{x^2} x 2 4 − x 2 using trigonometric substitution.
Find the indefinite integral of ∫ x 3 x 2 + 9 d x \displaystyle \int \frac{x^3}{\sqrt{x^2 + 9}} \, dx ∫ x 2 + 9 x 3 d x using trigonometric substitution.
Perform the substitution u = x + 1 u = x + 1 u = x + 1 and express the integral ∫ 1 − ( x + 1 ) 2 5 d x \displaystyle \int \sqrt{1 - (x + 1)^2}^5 \, dx ∫ 1 − ( x + 1 ) 2 5 d x in terms of u u u .
Perform the trigonometric substitution for the integral involving 1 + x 2 \sqrt{1 + x^2} 1 + x 2 .